LATERITISASI NIKEL PULAU PAKAL, KAB. HALMAHERA SELATAN PROVINSI MALUKU UTARA - Heru Sigit Purwanto; Sari Agustini (Jurnal Ilmiah MTG, 2014)
Laterite nickel study area in the southern part of the Pakal island is nickel mine owned by PT Antam ( presero ) Tbk , which has been done in mining ore for export .Ultramafic rocks are part of a series of regional ophiolite that formed as a plate collision obduction ocean crust on the island arc in the western Pacific plate. Minerals analysis with XRD and petrography are olivine and pyroxene which partially altered into serpentine as lizardite, chrysotile and talc. Olivine is a mineral that most carriers element Ni to 0.3 %. Ultramafic rocks classification based on mineral composition of olivine and piroksen are dunite and peridotite which is weak-strong serpentinize.Weathering process is strongly influenced by the origin of rock types, minerals and elements stability, mobilization ions, residual concentration and enrichment. Relative concentration of elements Mg and SiO2 which is inversely proportional to the mobile elements that are immobile Fe. Alteration of olivine and pyroxene due to weathering processes starts from the unstable nature altered into smectite in the saprolite and transition zone. Chrysopras is quartz vein that is formed on the associated with nickel saprolite zone between the boulders filled fractures. Serpentine and talc have altered slower and more stable at acidic pH but in alkaline pH more acid was forming secondary minerals such as oxidation minerals (hematite and gibbsite) and hydroxide minerals as goethite. Ni unstable in acidic pH was close to the surface and then tends to bind elements also form a ferro magnesian garnierite.Weathering process of unserpentine rocks was faster than serpentines rocks. The relative concentration of Ni in unserpentine rocks more than weak until strong serpentinize rocks, with a ratio of 3-6 : 2-3 .Enriched Ni > 1.5 % occurred in the saprolite zone and transition zone with Fe < 13 % , 14-21 % Mg , with a range of 0.03% Co. Concentration of nickel study area can be classified as a potential Hydrous silicate Deposits (saprolite zone) and Oxide deposite (zone limonite - transition), the fix system processing nickel laterite ore for study area is a combination of propagators pyrometalurgical and hydrometallurgy.